Simultaneous Real-Time Monitoring of Oxygen Consumption and Hydrogen Peroxide Production in Cells Using Our Newly Developed Chip-Type Biosensor Device - Prasad, Ankush; Kikuchi, Hiroyuki; Inoue, Kumi Y.; Suzuki, Makoto; Sugiura, Yamato; Sugai, Tomoya; Tomonori, Amano; Tada, Mika; Kobayashi, Masaki; Matsue, Tomokazu; Kasai, Shigenobu (Frontiers in Physiology, 2016)
All living organisms bear its defense mechanism. Immune cells during invasion by foreign body undergoes phagocytosis during which monocyte and neutrophil produces reactive oxygen species (ROS). The ROS generated in animal cells are known to be involved in several diseases and ailments, when generated in excess. Therefore, if the ROS generated in cells can be measured and analyzed precisely, it can be employed in immune function evaluation and disease detection. The aim of the current study is to introduce our newly developed chip-type biosensor device with high specificity and sensitivity. It comprises of counter electrode and working electrodes I and II. The counter electrode is a platinum plate while the working electrodes I and II are platinum microelectrode and osmium-horseradish peroxidase modified gold electrode, respectively which acts as oxygen and hydrogen peroxide (H2O2) detection sensors. Simultaneous measurement of oxygen consumption and H2O2 generation were measured in animal cells under the effect of exogenous addition of differentiation inducer, phorbol 12-myristate 13-acetate. The results obtained showed considerable changes in reduction currents in the absence and presence of inducer. Our newly developed chip-type biosensor device is claimed to be a useful tool for real-time monitoring of the respiratory activity and precise detection of H2O2 in cells. It can thus be widely applied in biomedical research and in clinical trials being an advancement over other H2O2 detection techniques.